2015
DOI: 10.1016/j.ypmed.2015.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Has recommended preventive service use increased after elimination of cost-sharing as part of the Affordable Care Act in the United States?

Abstract: Background An early provision of the Affordable Care Act (ACA) eliminated cost-sharing for a range of recommended preventive services. This provision took effect in September 2010, but little is known about its effect on preventive service use. Methods We evaluated changes in the use of recommended preventive services from 2009 (before the implementation of ACA cost-sharing provision) to 2011/2012 (after the implementation) in the Medical Expenditure Panel Survey, a nationally representative household interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 26 publications
4
55
0
Order By: Relevance
“…2024 These studies examined population trends without specifically identifying groups that were relieved of cost-sharing requirements. Two quasi-experimental studies, each using data from a single insurer, have reported mixed findings.…”
Section: Discussionmentioning
confidence: 99%
“…2024 These studies examined population trends without specifically identifying groups that were relieved of cost-sharing requirements. Two quasi-experimental studies, each using data from a single insurer, have reported mixed findings.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some studies found no effect of the elimination of cost-sharing for screening colonoscopies on participation in CRC screening (32–34), despite the fact that financial concerns is one of the most reported barriers for CRC screening. Substantial financial barriers may persist despite ACA provisions (a predicted 36% of procedures is still subject to coinsurance requirements), reflecting the complexity of current reimbursement policy for both patients and providers.…”
Section: Discussionmentioning
confidence: 99%
“…From 2009 to 2011, hypertension screening, cholesterol screening, and annual dental visits increased among young adults, though influenza vaccinations did not. 13 Early data hint at increased receipt of other preventive services for adults of all ages 14,15 as ACA provisions for expanded insurance coverage and no co-payments took effect.…”
Section: Introductionmentioning
confidence: 99%